The 'modern Botucatu' : the modern city representation in the Sao Paulo hinterland (1928-1934) - Oliveira, Eduardo Romero de [UNESP]; Martins Botaro, Luis Gustavo [UNESP] (Univ Estadual Londrina, 2018)
The article aims to approach the modernization of the urban area in the interior of Sao Paulo from the case study of the city of Botucatu between the years of 1928 to 1934. To do so, it was used the local newspapers (Correio de Botucatu, Jornal de Noticias and Folha de Botucatu) and their perception on the aspects and elements that categorize a modern city image. Among these elements, we highlight the use of electricity for commercial and daily purposes, the city's industries and the railways. However, with regard to transport and modernity, we held the hypothesis that the railway is not the only modernizing element: the presence of the car and the highways motorways is reaffirmed in the newspapers as a means of boosting trade and local industry, which are conditions for the modernization of the urban space of Botucatu, according to the newspapers.
Keywords: Botucatu; Urban infrastructure; Modernity; Railway; Automobile